Circ_0114427 promotes LPS-induced septic acute kidney injury by modulating miR-495-3p/TRAF6 through the NF-κB pathway - Lei Xu; Hongxia Cao; Peng Xu; Mingxi Nie; Chun Zhao (Taylor & Francis Group, 2022)
Backgrounds Septic acute kidney injury (AKI) is a severe illness in clinics. Enriching researches investigated the regulatory network of AKI during the past decades, evidences showed that circular RNAs (circRNAs) were involved in the molecular mechanism of human AKI. However, the special responses remain largely elusive. Thus, the study aims to investigate the function of circ_0114427 in the progression of AKI. Methods The levels of circ_0114427, miR-495-3p and Tumour Necrosis Factor Receptor-Associated Factor 6 (TRAF6) were both assessed by quantitative real-time polymerase chain reaction (qRT-PCR). In addition, lipopolysaccharide (LPS) was applied to establish AKI cell model, and 3-(4,5-dimethyl-2-thiazolyl)-2,5-diphenyl-2-H-tetrazolium bromide (MTT) assay was carried out to determine the viability of LPS-induced HK-2 cells. The expression of TRAF6, B-cell lymphoma-2 (Bcl-2), Bcl2-associated X (Bax), cleave-caspase 3, caspase 3, total IκBα (t-IκBα), phospho-IκBα (p-IκBα), total p65 (t-p65) and phospho-p65 (p-p65) were all detected via western blot. The levels of IL-1β and TNF-α were identified by western blot and ELISA. What's more, cell apoptosis was measured by flow cytometry. Lastly, dual-luciferase reporter, RNA Immunoprecipitation (RIP) and RNA pull-down assays were employed to verify the relationships between miR-495-3p and circ_0114427 or TRAF6 in vitro. Results The level of miR-495-3p was remarkably restrained while circ_0114427 and TRAF6 levels were specially reinforced in AKI patient serum samples and LPS-induced HK-2 cells. Moreover, IL-1β and TNF-α were highly expressed in LPS-induced AKI cells. Functionally, circ_0114427 was a sponge of miR-495-3p, and circ_0114427 silence-mediated effects in LPS-induced HK-2 cells were partly ameliorated by the addition of miR-495-3p inhibitor. Moreover, TRAF6 was a target gene of miR-495-3p, and the inhibiting effect of miR-495-3p on cell apoptosis and inflammatory response was mitigated by TRAF6 overexpression. Mechanistically, the circ_0114427/miR-495-3p/TRAF6 axis modulated cell apoptosis and inflammatory response via NF-κB/p65 signalling pathway in AKI. Conclusion Circ_0114427 regulated cell apoptosis and inflammatory response through miR-495-3p/TRAF6 axis via NF-κB/p65 signalling pathway, providing a novel mechanism in clinical treatment of AKI patients.Highlights Circ_0114427 is upregulated in serum specimens from septic AKI patients and LPS-induced HK-2 cells. LPS treatment suppresses cell viability and promotes apoptosis and inflammation in HK-2 cells. Circ_0114427 knockdown ameliorates the effects of LPS on cell viability, apoptosis and inflammation in HK-2 cells. Circ_0114427 regulates LPS-induced HK-2 cell injury by regulating miR-495-3p/TRAF6/NF-κB/p65 axis.